Patient-Level Predictors of Psychiatric Readmission in Substance Use Disorders - Böckmann, Volker; Lay, Barbara; Seifritz, Erich; Kawohl, Wolfram; Roser, Patrik; Habermeyer, Benedikt (Frontiers in Psychiatry, 2019)
Repeated psychiatric readmissions are a particular challenge in the treatment of substance use disorders and are associated with substantial burden for patients and their associates and for health care providers. Factors affecting readmission rates are heterogeneous and need to be identified to better allocate resources. Within the Swiss health care system such data on substance use disorder patients are largely missing. Understanding these factors might bear important implications for future health care planning. Thus here, we examine risk factors of inpatient readmission. We retrospectively analysed all admissions to the hospital's department of addictive disorders in the year 2016. Patients included in the study were followed over a period of one year after discharge regarding readmissions to the clinic. Besides the demographic, social and economic data we extracted data concerning patient history, admission and discharge as well as clinical data regarding type and number of substances abused and comorbid diagnoses. In order to describe severity of cases we furthermore included the scores of the Health of the Nation Outcome Scale (HoNOS) at admission and at discharge as documented in the medical database. Of the 554 patients included in the study, 228 (41.2 %) were readmitted within 12 months. Previous admissions, concomitant use of different substances, presence of psychosis or mania and a higher severity score at discharge increased the likelihood of readmission. The odds for readmission were furthermore higher in patients not being married, living alone and being unemployed. When all (bivariate) statistically significant factors are included into a logistic regression model, the previous number of admissions and the HoNOS clinical score at discharge significantly contribute to this model. Our findings stress that patients with higher symptom load at discharge are prone to be readmitted within 12 months. The same applies for patients with previous admissions. These findings suggest that the development of specific interventions to prevent premature discharge before satisfactory symptom remission, in particular in those patients with previous admissions in their patient history, might help to prevent readmissions.